An Intervening Maṣlaḥah on Influencing Reward and Punishment for Employee’s Performance: A Study at Warung Spesial Sambal Yogyakarta: Intervensi Maṣlaḥah dalam Mempengaruhi Reward dan Punishment Terhadap Kinerja Karyawan: Studi pada Warung Spesial Sambal Yogyakarta - Setiawan bin Lahuri; Gafita Almas; Ainun Amalia Zuhroh (El-Qist: Journal of Islamic Economics and Business (JIEB), 2023)
This study aims to examine the influence of reward and punishment factors on improving the quality of employees' performance and how the achievement of maṣlaḥah on reward and punishment factors for improving employee performance as an intervening variable at Waroeng Special Sambal. This study used a quantitative method with a sample of 76 respondents determined using a Technical Census, namely the Sample Census. Data was collected by distributing questionnaires and observations, then processed using the SmartPLS version 4 measuring tool, the PLS-SEM model. The study's results prove that punishment has a moderate effect on performance. The effect of reward on performance is significantly positive with a value of 0.406 and P values of 0.024, where if rewards are often appropriately applied, then employee benefits in work also increase found that the effect of punishment on performance is significantly positive with a value of 0.561 and P values 0.002 where if punishment is often appropriately applied, employee benefits in work also increase. So, the achievement of maṣlaḥah still significantly acts as a variable that mediates the indirect effect of reward and punishment for improving employees’ performance.